The phenomenon of violence against women and children in Lampung Province: Demography of victims, perpetrators, and events - Wati, Lia Sita; Wuryaningsih, Caroline Endah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2019)
Cessation of Violence against women and children is a target that must be achieved by 2030 (SDG’s). An increase in violence cases in Lampung since 2015-2017 rose from 41 to 272 cases. The purpose of this research was to determine the phenomenon of acts of violence against women and children: demographics, victims, perpetrators, incidents, related factors and variables that most influence the incidence of violence. The research used secondary data in the Online Information System for the Protection of Women and Children (SYMPHONY-PPA) of the Lampung Empowerment and Child Protection Office in 2018 totaling 273 cases. The design uses cross sectional, then tested using chi square and multiple logistic regression with a significance level of 95 percent. Types of violence were sexual violence 188 (79.3 percent), female victims 203 (87.9 percent), child victims 181 (76.4 percent), age of victims 13-17 years 97 (40.9 percent). As a result of trauma violence (96.2 percent). 230 male (97 percent), age 25-44 years 92 (38.8 percent), adult age 207 (87.3 percent), 55 neighbors (23.2 percent), outside perpetrators 156 (65.8 percent). Pause-report less than 7 days 121 (51.1 percent), location of the incident at home 167 (70.5 percent). The biggest services for victims are complaints and 75 health services (32.5 percent). There is a relationship between the age of the victim (child-adult) (p = 0.003) OR = 2.9 (1.4-5.7), the relationship between the perpetrator and the victim (p = 0,001) with the type of violence experienced. The age of the victim is the most dominant variable with violence (B exs = 2.2), there is an interaction of the victim-perpetrator relationship with the event-report interval.